Antiviral Activity of Crataegus azarolus Extract Against Herpes Simplex Virus Type 1 - Zhang Ming; Chen Yu; Liu Fang (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Background: due to the spread of infections caused by the herpes simplex virus and the occurrence of antiviral resistance, many studies are conducted to obtain alternative treatments with better performance and fewer side effects. This research was carried out to measure the phenolic and flavonoid content of extracts obtained from Crataegus azarolus (C. azarolus) leaves and flowers and to investigate the antiviral effect of this plant on herpes simplex virus type 1 in cell culture. Methods: In this study, the phenolic and flavonoid content of extracts received from hawthorn leaves and flowers was measured using a Cary 300 UV-Vis spectrometer. The MTT technique was used to examine the toxicity of C. azarolus extract in Vero cells. The effect of the extract against herpes simplex virus type 1 (HSV-1) was then tested at various concentrations. Results: Compared to the flower extract, C. azarolus leaf extract has a much higher total phenolic and flavonoid content. The fifty percent cytotoxic for C. azarolus leaf and flower extracts was 1203 and 870 g/ml, respectively. Flower and leaf extracts were revealed to have antiviral activities of 9.50 and 10.41, respectively. Conclusion: The active components in hawthorn leaf extract help minimize the replication of herpes simplex virus type 1.